2019
DOI: 10.29333/iejme/5769
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inductive Reasoning in Middle School Mathematics Teachers in a Generalization Task

Abstract: This paper reports on the characterization of the inductive reasoning used by middle school mathematics teachers to solve a task of generalization of a quadratic pattern. The data was collected from individual interviews and the written answers to the generalization task. The analysis was based on the representations and justifications used to move from particular cases to the formulation of the general rule. Three processes characterize the inductive reasoning of the mathematics teachers to obtain a general r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The statistical test stage was used to conclude. Students must be able to communicate statistical test results into real problems, understand parameter estimation by statistics, understand sample generalization to the population, and think inductively [33][34][35][36][37]. The work from making hypotheses to concluding is the mental action of a student's WoT.…”
Section: Resultsmentioning
confidence: 99%
“…The statistical test stage was used to conclude. Students must be able to communicate statistical test results into real problems, understand parameter estimation by statistics, understand sample generalization to the population, and think inductively [33][34][35][36][37]. The work from making hypotheses to concluding is the mental action of a student's WoT.…”
Section: Resultsmentioning
confidence: 99%
“…This makes students fail to remember the concepts used in solving problems [15]. The first step that must be done is internal structuring by identifying mathematical objects only consist of basic problems to get the characteristics of the problem [18].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that students had difficulty observing regularity, patterns and formulation of generalizations [15]. Students can make mistakes at every stage of structuring, mapping, applying, or verifying.…”
Section: Introductionmentioning
confidence: 99%
“…A nivel universitario, se establecen múltiples conexiones con otros temas matemáticos como las funciones, series y límites (ARTIGUE, 1995;SIERPINSKA, 1990) y existe una amplia gama de aplicaciones en distintas disciplinas, por ejemplo, en física, biología, economía, medicina y otras (JONES, 2011). Sin embargo, existen estudios enfocados en el razonamiento, la comprensión y la generalización de patrones, donde se evidencian que los estudiantes y profesores manifiestan dificultades para resolver situaciones matemáticas que involucran a las sucesiones (MANFREDA;SLAPAR;HODNIK, 2012;BECKER, 2007;SOSA;APARICIO;CABAÑAS-SÁNCHEZ, 2019;WILKIE, 2021).…”
unclassified